Analysis of the Seaweed Day Cream Product Buying Intention: Theory of Planned Behavior Approach - Putri, Ayulia Karisma; Retnaningsih, Retnaningsih (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
Seaweed is one of the abundant and widely used marine resources which has been popular as of the basic materials of cosmetics and skin care, such as day cream. The study aimed to analyze the intention to buy seaweed day cream product manufactured by Bogor Agricultural University (IPB) and sold at Serambi Botani, Indonesia, using the Theory of Planned Behavior approach including attitude, subjective norms, and behavioral control. The data were collected from 400 female students of IPB who were selected randomly as participants and the office staffs of Serambi Botani. Students were asked to fill in the structured questionnaire with self-report methods while the staffs were interviewed about the seaweed day cream product. The findings showed the attitude of students toward seaweed day cream product was identified fair, yet the subjective norms and behavioral control were low. Thus, the majority of IPB students was not interested in buying the product.